DAMPAK PEREDARAN PRODUK CAKRAM OPTIK ISI (CD DAN VCD) BAJAKAN DI KOTA SURABAYA - Aprianti, Duwi; -, Marwanto (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
The phenomena which often happen in a creation of an art is copyright piracy, particularly in a product of optic disc in media visual product. This situation, create a bad impact for the artist nor the producer, who suffera financial lost in Indonesian. Indonesian government should concern of this situation, and must involve in to this piracy situation.
Keywords: Intellectual Prosperity Right, CopyRight, Optic Disc, Piracy.